GEOLOGICAL CONSIDERATION FOR CO2 STORAGE IN INDONESIA: A BASINAL SCALE OUTLOOK - Hendra Amijaya (Journal of Applied Geology, 2015)
Carbon dioxide capture and storage (CSS) is alternative of reducing atmospheric emissions of CO2. The concepts of CO2 storage refer to the injection of carbon dioxide in dense form into aquifers, which basically must meet several conditions. Three types of geological formations that can be used for the geological storage of CO2 are oil and gas reservoirs, deep saline formations and unmineable coal beds. Indonesia has 60 Tertiary basins, however that great precautions must be taken for selecting particular sedimentary basin in Indonesia for carbon dioxide storage because of high possibility of leakage and the need to find deep formations as CO2 host since the geothermal gradient is high. One possibility to find proper basins is by selected “mature” basin as the detailed geological conditions are well known. Candidates are are North East Java or South Sumatra Basins. Keywords: Carbon dioxide capture, storage, emission, basin.